Purification of algnic acid by Local isolate of Azotobacter Vinelandi - Mahdi, J.I.; Ali, M.R.; Hamza, H.M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The bacteria Azotobacter Vinelandii  was taken from a central research in Baghdad, The purification of alginic acid which produced from the bacteria by several steps starting with precipitation with isopropanol (3:1) v/v , Washing by ppt with 100ml of isopropanol       : distilled water (3:1) v/v , then the ppt was dissolved in warm distilled water and dialysis against distilled water from 24 h/s . To Complete the purification , gel filtration chromatography was conducted on sephacryl s-100 column followed by ion â€“ exchange chromatography . Using DEAE cellulose column . The molecular Weight of purified al ginic acid was higher than that of blue dextran 2000,It was more than (2) millions Dalton .